2004
DOI: 10.1213/01.ane.0000105868.84160.09
|View full text |Cite
|
Sign up to set email alerts
|

The Supraclavicular Block with a Nerve Stimulator: To Decrease or Not to Decrease, That Is the Question

Abstract: When nerve blocks are performed with a nerve stimulator, it is customary to reduce the nerve stimulator output to <= 0.5 mA before injecting. Apparently this is not necessary with a supraclavicular block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Because in all cases the solution reached within 0.5 mm of the nerve, successful block would likely have been achieved in all injections regardless of final stimulation threshold, because the larger volumes of clinical injections would provide a source from which diffusion of local anesthetic would ultimately block conduction. These anatomical results suggest that threshold differences in this range are not clinically relevant, as has been reported in studies of efficacy in patients 9,13,14…”
Section: Discussionsupporting
confidence: 66%
“…Because in all cases the solution reached within 0.5 mm of the nerve, successful block would likely have been achieved in all injections regardless of final stimulation threshold, because the larger volumes of clinical injections would provide a source from which diffusion of local anesthetic would ultimately block conduction. These anatomical results suggest that threshold differences in this range are not clinically relevant, as has been reported in studies of efficacy in patients 9,13,14…”
Section: Discussionsupporting
confidence: 66%
“…Electrical nerve stimulation is still commonly used as a nerve localization technique when performing peripheral nerve blocks . The relationship between needle‐nerve proximity and the applied current during electrical nerve stimulation has been challenged . Appropriate needle‐nerve proximity for local anesthetic injection is assumed when an evoked motor response occurs with minimal stimulation currents between 0.3 and 0.5 mA .…”
mentioning
confidence: 99%
“…Secondly, a safe needle‐nerve distance is favored in order to avoid needle‐induced nerve trauma – i.e., direct needle‐nerve contact (NNC) or nerve perforation . Clinical data have shown that current thresholds of 0.9 mA also result in a successful nerve block . Further clinical trials have described NNC without evoked motor response at current intensities of approximately 0.5 mA, whereas failed motor response was not observed for current intensities of 1 mA .…”
mentioning
confidence: 99%
“…Furthermore, no difference was noted in terms of onset or duration of anaesthesia. 11 In majority of grade 1 sensory block, ulnar nerve sparing was found with both the approaches, i.e. 5 cases in group C and 7 cases in group L. Failure to block the lower trunk, which subsequently results in inadequate ulnar nerve anaesthesia as lower trunk commonly lies in the 'corner pocket' between the first rib inferiorly, the supraclavicular artery medially and the nerves superiorly frequently produces incomplete block while using the supraclavicular approach.…”
Section: Discussionmentioning
confidence: 88%
“…Complete sensory block was achieved in 76.66% of patients in group C and 70 % of patients in group L. Remaining patients developed grade I sensory block. To achieve a higher success rate, Franco et al (2004) recommended to use 0.5 mA as minimal stimulatory currents to obtain a motor response (finger flexion or extension) prior to injection of local anaesthetics. Furthermore, no difference was noted in terms of onset or duration of anaesthesia.…”
Section: Discussionmentioning
confidence: 99%